Registro de Euchroma gigantea (Linnaeus, 1758) (Coleoptera: Buprestidae) para tres departamentos de la región Caribe Colombiana. - Alvarez García, Deivys Moises; Arroyo Pérez, Wendy Yohana; Navarrete Iriarte, Luis Eduardo (Instituto de Ecología, A.C., 2014)
We present a new geographical record of the giant metallic beetle, Euchroma gigantea (Buprestidae), in Córdoba, Sucre and Bolívar in the Caribbean Region of Colombia.